A Brief Summary of Current Therapeutic Strategies for Spinal Cord Injury. (June 2022) - Yao, Chun; Tang, Xin; Cao, Yuqi; Wang, Xuhua; Yu, Bin
Abstract: Spinal cord injury (SCI) is a tremendous disaster in a person's life. It interrupts the brain–body neuronal circuits, resulting in functional deficits. Pathogenesis of SCI is a progressive and comprehensive event. In clinical trials, attempts to promote nerve regeneration and functional recovery after SCI have met with failures. Recently, with the development of transcriptome sequencing and biomaterials, researchers have struggled to explore novel efficient therapeutic treatments for SCI. Here, we summarize the recent progress that has been made in SCI repair based on the lesion microenvironment, neural circuits, and biomaterial scaffolds. We also propose several important directions for future research, including targeted-microRNA therapy, blood vessel interventions, and multiple treatment combinations. In short, we hope this review will enlighten researchers in the field and pave the way for SCI therapy.